Undiagnosed Chronic Granulomatous Disease, Burkholderia cepacia complex Pneumonia, and Acquired Hemophagocytic Lymphohistiocytosis: A Deadly Association - Maxime Maignan; Colin Verdant; Guillaume F. Bouvet; Michael Van Spall; Yves Berthiaume (Case Reports in Pulmonology)
Background. Chronic granulomatous disease is a rare inherited disorder of the phagocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. The clinical course of the disease is marked by recurrent infections, including Burkholderia cepacia complex infection. Case Report. Here we report the case of a 21-year-old male hospitalized for a Burkholderia cepacia complex pneumonia. Despite the broad spectrum antibiotic treatment, fever continued and patient’s condition worsened. Anemia and thrombocytopenia developed together with hypofibrinogenemia. The patient died of multiple organ dysfunction 17 days after his admission. Autopsy revealed hemophagocytosis, suggesting the diagnosis of acquired hemophagocytic lymphohistiocytosis. DNA analysis showed a deletion in the p47phox gene, confirming the diagnosis of autosomal recessive chronic granulomatous disease. Discussion. In addition to chronic granulomatous disease, recent findings have demonstrated that Burkholderia cepacia complex can decrease activity of the NADPH oxidase. Interestingly, hemophagocytic lymphohistiocytosis is characterized by an impaired function of the T-cell mediated inflammation which is partly regulated by the NADPH oxidase. Physicians should therefore pay particular attention to this deadly association.